Why Nurses Excel: The Role of Work Environment and Motivation - Syarif, Arman (Penerbit Goodwood, 2025)
Purpose: This study investigates the effect of work environment on nursing performance, with work motivation as a mediating variable. It focuses on nurses working in public health centers (Puskesmas) in Batam, Indonesia. Methodology/approach: A cross-sectional survey was conducted involving 136 nurses using a structured questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Results/findings: The results revealed that the work environment had no direct effect on nursing performance. However, it showed a significant indirect effect through work motivation. Motivation was found to fully mediate the relationship between the work environment and nurse performance. Conclusions: A supportive work environment contributes to nursing performance only when it enhances work motivation. Motivation serves as the primary driver in translating organizational support into effective job behavior, particularly in the public healthcare context. Limitations: This study emphasizes the psychological mechanism through which work environment affects performance, supporting the integration of motivational strategies in nurse management. It offers practical implications for improving performance in primary care institutions by focusing on internal motivational factors. Contribution: The cross-sectional design limits the ability to draw causal inferences. The reliance on self-reported data may introduce bias, and the findings are specific to Puskesmas in Batam, thus limiting generalizability to other regions or healthcare settings.